Experimental and DFT investigations on L Proline Adipate NLO single crystals. (2022) - Indumathi, N.; Deepa, K.; Victor Antony Raj, M.; Senthil, S.
Abstract: Optically transparent L-Proline Adipate (LPA) single crystal has synthesis by slow evaporation solution growth technique (SEST) method at ambient condition. The crystallinity of LPA crystal was examined by powder XRD analysis, which crystallizes in the monoclinic system. The various functional groups were identified by FTIR spectra and it compares with a simulated spectrum of LPA by using DFT/B3LYP 6–311++G(d, p) set. The Photoluminence spectrum (PL) was used to determine the optical properties of LPA. The Vickers microhardness measurements reveal the crystal possesses soft category of mechanical strength. The determined HOMO-LUMO value shows the crystal is chemically active and charge transfer occurs within the molecule. The linear polarizability (α) and 1st order hyperpolarizability (β) values of LPA have been investigated.